Odpowiedzi

2009-12-01T22:02:26+01:00
A) (x+5)*(x-2) = x²+3x-10
b)1/2*(x+3)*(x-3) = (0,5x+1,5)*(x-3)=0,5x²-1,5
c)(x+x+2)*x+1/2=(2x+2)*x+1/2 = x*(x+1)=x²+x




2009-12-01T22:05:23+01:00
P=a×b=(x+5)(x-2)=-2x+5x-10=x²+3x-10
b)P=a×h₂=(x+x-3)₂=x²-3x+3x-9₂=x²-9₂
c)P=(a+b)×h₂=(x+2+x)(x+1)₂=(2x+2)(x+1)₂=2x²+2x+2x+2₂=2x²+4x²+2₂=x²+2x+1
2009-12-01T22:07:12+01:00
A )
P=2(x-2) +2(x-5)
2x-4+2x-10
4x-14

b)
[(x+3)(x-3)0.5
x(do potęgi 2)-3x+3x-9
___________________________
2
x(dopotęgi 2)-9
____________________
2

c)
(x+x+2)*(x+1)
____________-
2

2x(po potęgi2)+2x+2x+2
_________________________
2
2x(do potęgi2)+4x